(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Throughout the history of international relations, armed conflicts continue to evolve in parallel with thoughts and philosophies. Heads of State in the “race” for new weapons and war technologies, sometimes, neglect the well-being of the well-being of their peoples. It was essential, even in the last century, as a way to contain the excesses committed by the parties in combat situations, to typify war in international law. This article addresses the intervention of international humanitarian law in Israel’s international armed conflicts, in the Middle East, against the Gaza Strip. Its general objective is to verify the historical factors that motivated the conflicts in the Middle East. The specific objective is to verify the action of the United Nations as an international body whose mission is to maintain world peace. The result of the survey sheds light on whether Israel, under humanitarian law, can bomb civilian areas, in Gaza, on the grounds that they are military targets. Also, if Israel maintains control of the water supply in Gaza as a combat tactic.